Employers and employees: power and class relations in Brazilian society and the teaching of Brazilian literature and Portuguese to foreigners - Fernandes, Joyce; Alvares Rosal Botler, Lais Maria (BELT - Brazilian English Language Teaching Journal, 2019)
In Brazilian literature, there are representations of class relations that lead us to reflection through a critical construction regarding the roles that these relations have in society. Our intention is to reflect on teaching approaches of the existing relations between employers and employees in Brazilian society, from the experience report on the teaching practice of two lecturers, in classes of language and Brazilian literature to foreigners. We will analyze these relations in Dois Irmãos, by Milton Hatoum, O Auto da Compadecida, by Ariano Suassuna, and chronicles by Clarice Lispector published in the book A Descoberta do Mundo, founded on a teaching approach based on the dialogic method by Hayes (1990), which focuses on the development of students’ critical thinking. The topic has been shown to be fruitful in teaching Portuguese as a foreign language, as it allowed to be extended to other Brazilian cultural and historical issues, enriching the learning process.